The value of liability tests in abuses of dominance - Mariateresa Maggiolino (Market and Competition Law Review)
Currently, there is a debate in the European Union regarding the European Commission’s approach in assessing the behaviour of dominant firms. It is argued that as digital ecosystems become more powerful, there is increasing pressure on the Commission to act against their practices, regardless of whether they meet the test established by the European Courts to find out liability. This article aims to demonstrate that the Commission’s approach, which occasionally deviates from liability tests, is legitimate, because it aligns with the effects-based notion of abuse and the teleological interpretation of treaty rules. Moreover, this article maintains that if such liability tests were unalterable, their individual components would be elevated to essential elements of the concept of abuse, which directly contradicts the current interpretation of this notion. Finally, the article asserts that the liability tests used thus far represent a collection of factual circumstances that hold substantial evidential value in demonstrating the effects of dominant firms’ practices. It however acknowledges that, while this evidential value has remained high over time, it may still vary depending on the circumstances. This is why the particular circumstances that make up the elements of these tests can be substituted with alternative circumstances, depending on the specific scenario being analysed.